Implementasi Alokasi Memori Dinamis pada Sistem Komputer Berbasis Clustering K-Means - Florensius Tri Putra Simamora; Widhi Yahya; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Virtualization is the process of creating forms in virtual versions of operating systems, networks and others that can run applications like physical devices. Resources in virtualization become an important factor to support server performance. Sometimes resources are not fully utilized when resource allocation remains. As a result, when the server requires more resources, unused memory allocations can not be used. With memory allocation, the system can manage memory usage to maintain and improve server performance that can sometimes change. Application of memory allocation can be facilitated by algorithm and k-means regression method to predict the use of memory resources. To that end, the authors have implemented a dynamic memory allocation system on computer-based k-means clustering system. From the test results, the system is able to make changes in the form of upgrades and downgrades with the help of tools Apache Jmeter with time 2.5 seconds. Based on the results of tests that have been done, hypervisor successfully upgraded at 36.5699 seconds from 1 GB to 2 GB. Then second to 153.1348 hypervisor upgrade again from 2 GB to 4 GB. After the request to the server stops, the hypervisor downgrades the seconds to 611.709 from 4 GB to 2 GB then downgrade again in seconds to 624.4994 from 2 GB to 1 GB.